“FAKTOR-FAKTOR (UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, JENIS INDUSTRI, DAN OPINI AUDITOR) YANG MEMPENGARUHI AUDIT DELAY DI INDONESIA” (Studi Empiris Pada Perusahaan LQ-45 Yang Tetrdaftar di Bursa Efek Indonesia Periode 2011-2015) - Rika Fatmawati (Universitas Islam Malang, 2017)
AbstractThis research aimed to simultaneously and partially analyze the influence of companysize, profitability, solvency, type of industry, and auditor opinion toward Audit Delay of theLQ-45 companies listed in Indonesia Stock Exchange. The method of this research wasdescriptive, classical assumptions and the population was all of LQ-45 companies listed inIndonesia Stock Exchange on the period 2011-2015. Data was collected by the method ofpurposive sampling and statistically analyzed through logistic regression analysis. The resultshowed that there was a simultaneous influence between company profitability, solvency, typeof industry and auditor opinion of the LQ-45 companies Audit Delay. In the other hand, therewas a positive signifikan partial influence between company profitability of LQ-45 companiesAudit Delay. There was negative signifikan partial influence between company solvency andthe type of industry of LQ-45 companies Audit Delay. no partial influence between size,auditor opinion of the company toward Audit Delay of the go public LQ-45 companies listedin Indonesia Stock Exchange 2011-2015.Keywords: Audit Delay factors, Financial report, LQ-45 Companies, Stock exchange